Pemanfaatan Limbah Cair Tahu sebagai Bahan Baku Pembuatan Pupuk Organik Cair Menggunakan Teknik Fermentasi - Haerani, Rosita; Supriyanto, Supriyanto; Febrinasari, Tantry (DPPM UNIVERSITAS PELITA BANGSA, 2022)
The rapid growth of the tofu industry is not independent of the environmental impacts caused by the tofu liquid waste produced. Tofu liquid waste contains high organic C, causing high concentrations of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solids (TSS). The high organic C content indicates that there are many organic materials in tofu liquid waste but it has not been optimally utilized as a raw material to make liquid organic fertilizer. This research aims to utilize tofu liquid waste as a raw material for making liquid organic fertilizer and determine the concentration of important macronutrients contained in liquid organic fertilizer from tofu liquid waste. The study method used is a quantitative method, carried out by making liquid organic fertilizer using a fermentation process and then testing the concentration of N, P and K in the fertilizer that has been made. The results of the study show that the content of important macronutrients contained in liquid organic fertilizer from tofu liquid waste is N at 0.4%, P at 0.132% and K at 0.296%.